Wireless Echo Friendly Communication System for Future Broad Band Applications - Murali Kalipindi; K. Prasuna (Society of Visual Informatics, 2018)
Our aim is to build an eco-friendly system for the assortment of information from the environment. The system must be power-independent with the usage of renewable power bases. As a holdup different resources in power source in the event of critical conditions, other ecological technologies can be used. Our proposed system needs to be power efficient and should be able to accomplish itself without any exterior observation.